POTENSI PAKAN HASIL LIMBAH JAGUNG (Zea mays L.) DI DESA BRAJA HARJOSARI KECAMATAN BRAJA SELEBAH KABUPATEN LAMPUNG TIMUR - I Wayan Ardiana K; Yusuf Widodo; Liman . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The aim of research is : 1) determine the potential of waste corn that can be used as feed in Harjosari Braja Village, Braja Selebah Sub-District, East Lampung 2) aware the potential capacities of livestock from waste corn in Harjosari Braja Village, Braja Selebah Sub-District, East Lampung. The research was conducted in February to March 2015, located in the Braja Harjosari village. The methode of research used survey with simple random sampling. The results showed that the availability of feed corn waste based on the land area of 52 hectares in the Braja Harjosari village, existing corn waste production in Braja Harjosari village was 623.938,3 kg / year of dry matter or 623,94 tons / year. On the utilization of waste corn as feed if the usage as much as 30% and 40% in the ration consecutively produce carrying capacity as much as 417,44 UT / year and 313,08 UT / year. (Keywords: Braja Harjosari Village, Corn Waste Production, Carrying Capacity).